Deeply Dissected Tundra Polygons on a Glacio-Fluvial Outwash Plain, Northern Ungava Peninsula, Québec - Gray, James; Seppälä, Matti (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTDeeply dissected tundra polygons are described from the continuous permafrost environment of northernmost Ungava. They are developed on a glacial outwash plain, formed subsequent to déglaciation of the site about 7,500 BP. The exposed surfaces of the polygons are sparsely vegetated and aeolian deflation has removed their sandy matrix material. The furrows between the polygons attain depths of 0.5-2 m. From the base of one. a 0.25 m wide wedge of peat and sandy material penetrates to a minimum depth of 0.7 m (the frost table depth). Radiocarbon dates of 1650 ± 60 BP and 740 ± 80 BP indicate that progressive filling of this fissure accompanied decay of a preexisting ice-wedge. The present low mean annual air temperature at the site ( - 70C) suggests that thawing of the ice-wedges may be related more to local dynamic factors, such as deflation and improved local drainage associated with fluvial dissection, than to regional climatic amelioration. Wedge ice is believed to still underlie the polygon furrows.